Aberrant frequency of IL-35 producing B cells in colorectal cancer patients. (February 2018) - Wang, Ke; Gong, Hui; Chai, Rui; Yuan, Hang; Chen, Yanxia; Liu, Jinlin
Abstract: Background: The IL-10 dependent regulatory function of B cells had recently more and more investigated and play important roles in cancer immunity, however, beyond IL-10 whether other inhibitory cytokines play an important role in cancer is lacking. Here, we investigated the role of IL-35 producing B cells in colorectal cancer (CRC). Methods: Thirty-two healthy controls (HC) and 49 untreated CRC patients were enrolled and the IL-35 producing B cells in the peripheral blood were investigated. Additionally, CD4 + CD25 +/high CD127 low/− regulatory T (Treg) and CD14 + HLA-DR low/− myeloid‑derived suppressor cells (MDSCs) were also investigated. Results: Results show that IL-35 producing B cells were significantly upregulated during the clinical progression of CRC, and negatively correlated with CD3 + T cell, positively correlated with the frequency of CD4 + CD25 +/high CD127 low/− Treg cells and CD14 + HLA-DR low/− MDSCs of these CRC patients. Conclusions: Together, IL-35 producing B cells were significantly elevated in CRC, indicating this B cell subset might participate in the immune suppression of CRC.